Advanced Computing in Industrial Mathematics Revised Selected Papers of the 10th Annual Meeting of the Bulgarian Section of SIAM December 21-22, 2015, Sofia, Bulgaria - Georgiev, Krassimir; Todorov, Michail; Georgiev, Ivan.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book presents recent research on Advanced Computing in Industrial Mathematics, which is one of the most prominent interdisciplinary areas and combines mathematics, computer science, scientific computations, engineering, physics, chemistry, medicine, etc. Further, the book presents the tools of Industrial Mathematics, which are based on mathematical models, and the corresponding computer codes, which are used to perform virtual experiments to obtain new data or to better understand the existing experimental results. The book gathers the peer-reviewed papers presented during the 10th Annual Meeting of the Bulgarian Section of SIAM (BGSIAM) from December 21 to 22, 2015 in Sofia, Bulgaria.
Factorizations in Special Relativity and Quantum Scattering on the Line -- Decision Support Tool in the project LANDSLIDE -- Generalized Nets as a Tool for Modelling of Railway Networks -- On nonlocal models of Kulish-Sklyanin type and generalized Fourier transforms -- Standing waves in systems of perturbed Sine-Gordon equations -- Stability Analysis of an Inﬂation of Internally-pressurized Hyperelastic Spherical Membranes Connected to Aneurysm Progression -- New Bounds for Probability of Error of Coded and Uncoded TQAM in AWGN Channel -- Construction of multistage scenario tree for insurance activity -- Microphone Array for Non-Contact Monitoring of Rolling Bearings -- Geothermal Effects for BOD Removal in Horizontal Subsurface Flow Constructed Wetlands: A Numerical Approach -- Further Results of Mean-Value Type in mat hbbC and R -- Computer Aided Modeling of Ultrasonic Surface Waves Propagation in Materials with Gradient of Properties -- InterCriteria Analysis of Simple Genetic Algorithms Performance -- Interval Algebraic Approach to Equilibrium Equations in Mechanics -- InterCriteria Analysis of Relations between Model Parameters Estimates and ACO Performance -- Newtonian and Non-Newtonian Pulsatile Blood Flow in Arteries with Model Aneurysms -- Reduced Rule-Base Fuzzy-Neural Networks -- Accuracy of linear craniometric measurements obtained from laser scanning created 3D models of dry skulls -- Equivalence of Models of Freeze-Drying -- Comparing Bezier curves and surfaces for coincidence -- Spectral theory of sl(3, C) auxiliary linear problem with Z2 × Z2 × Z2 reduction of Mikhailov type.
Keywords: Computational intelligence; Artificial intelligence; Mathematical models; Chemistry, Physical and theoretical; Computational Intelligence; Artificial Intelligence; Mathematical Modeling and Industrial Mathematics; Theoretical Chemistry